Malawi : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
The objective for net foreign assets was discussed in this paper. Macroeconomic performance under the PRGF arrangement was broadly discussed. Several developments during the second half of 2005/2006 required the authorities to strengthen financial management controls and to make other policy adjustments. To meet additional humanitarian needs, the government expanded its food security operations. The authorities are working with IMF staff and other stakeholders to redefine pro-poor spending for 2006/2007. The government has taken further steps to ensure the viability of the pension system.